2008
DOI: 10.1016/j.ccm.2007.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Screening with CT

Abstract: Lung cancer is the leading cause of cancer death in the United States. In 2007, it is estimated that 160,390 lung cancer deaths will occur in the US, representing 29% of all cancer deaths (1). Roughly 87% of lung cancers are attributed to cigarette smoking (2). Although cancer risk is attenuated by smoking cessation, the risk is not eliminated, and lung cancer now occurs with equal frequency in current and former smokers (3). Moreover, other factors clearly influence risk, including age; family history; chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 62 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…Although the majority of patients who developed lung cancer had airway obstruction and emphysema, a small proportion had emphysema alone. Finally, previous CT screening studies have not yet reported on the impact of radiographically detected emphysema in lung cancer risk [48].…”
Section: Chronic Obstructive Pulmonary Disease and Inflammationmentioning
confidence: 99%
“…Although the majority of patients who developed lung cancer had airway obstruction and emphysema, a small proportion had emphysema alone. Finally, previous CT screening studies have not yet reported on the impact of radiographically detected emphysema in lung cancer risk [48].…”
Section: Chronic Obstructive Pulmonary Disease and Inflammationmentioning
confidence: 99%
“…These techniques have some drawbacks, such as being expensive and having low sensitivity for identifying cancer cells at early stages. Annual CRG was reported as not helpful in reducing the mortality of lung cancer [ 16 ]. CT has been considered as the gold standard lung screening tool, which offers information of tumor features such as size, characterization and tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Bach is correct that the references we cited to support the statement that the median length of follow-up for the National Lung Screening Trial (NLST) is 4 years do not directly provide this information. The follow-up time for the NLST is 4 -6 years, as was recently confirmed by the principal investigator of the NLST [7], not the 5-7 years as stated by Bach. We estimated that the median follow-up time would be further shortened and closer to 4 years, because the NLST protocol [8] calls for information regarding cause of death to be obtained from the National Death Index, which is usually not available until one and a half years after the death has occurred.…”
mentioning
confidence: 64%